Composition Designing of Cooked Sausage "Udachnaya" Based on Optimization Principles - A. Diner , Yulia; A. Yurk, Natalia; V. Kosenchuk, Olga; V. Skryabina, Olga; S. Ryabkova, Dina (KnE Life Sciences, 2021)
This article deals with the process of composition designing of the cooked sausage "Udachnaya" by adding non-meat ingredients to reduce material costs for production, obtain a product with given chemical composition and technological properties, as well as to minimize the occurrence of defects characteristic of cooked sausage products, in particular broth-fat runoffs. As part of the research, complete preparations of the new generation “Biophos 90” and “Bioton gel 651” were used, which did not reduce the nutritional and biological value of meat products and also produced sausage products with high organoleptic and technological properties that are safe for consumer health and the environment. Synthesis of lessons learned in the development of the rational formulation of cooked sausage products shows that the use of mathematical modeling makes it possible to implement a targeted combination of ingredients and deliver the specified chemical composition and variable processing properties with an insignificant change in prime cost. The study was conducted using the technical base and laboratory areas of the Department of Commodity Research, Standardization and Quality Control (Faculty of Animal Science, Commodity Research, and Standardization), as well as the common use center of scientific equipment of FSBEI HE “Omsk State Agrarian University named after P.A. Stolypin”. The analytical data presented in this publication may be of interest to students of industry-specific colleges, as well as specialists in the meat industry, and can be implemented in real enterprises. Keywords: Construction, composition, cooked sausage, nutrient additives